Existence and Uniqueness of Solutions to Fractional Differential Equations in the Frame of Generalized Caputo Fractional Derivatives - Gambo, Y. Y.; Ameen, R.; Jarad, Fahd; Abdeljawad, T. (Springer, 2018)
The generalized Caputo fractional derivative is a name attributed to the Caputo version of the generalized fractional derivative introduced in Jarad et al. (J. Nonlinear Sci. Appl. 10:2607-2619, 2017). Depending on the value of. in the limiting case, the generality of the derivative is that it gives birth to two different fractional derivatives. However, the existence and uniqueness of solutions to fractional differential equations with generalized Caputo fractional derivatives have not been proven. In this paper, Cauchy problems for differential equations with the above derivative in the space of continuously differentiable functions are studied. Nonlinear Volterra type integral equations of the second kind corresponding to the Cauchy problem are presented. Using Banach fixed point theorem, the existence and uniqueness of solution to the considered Cauchy problem is proven based on the results obtained.
Abdeljawad, Thabet/0000-0002-8889-3768; Gambo, Yusuf Ya'U/0000-0002-3954-3200; Jarad, Fahd/0000-0002-3303-0623
Keywords: Generalized Caputo Fractional Derivative; Existence And Uniqueness; Cauchy Problem